Buddhist Meditation - (Khotmoon), PhramahaEkkachai; ., PhakruPariyattiphattanabundit (Journal of Graduate MCU KhonKaen Campus, 2025)
This book review aims to analyze the key concepts and values of Buddhist Samadhi, which presents meditation practices based on Buddhist principles. The book has been published 28 times by Wat Yannawetkhawan Publishing House, Nakhon Pathom Province. Its content is divided into three main chapters: (1) fundamental concepts of Buddhist meditation, (2) proper methods of meditation practice, and (3) ways to prevent and overcome the negative effects of meditation The analysis reveals that samadhi refers to a state of mental stability, concentration, and clarity, which serves as a foundation for personal and spiritual development. Meditation promotes inner peace, happiness, and mental clarity. It can also effectively help alleviate psychological problems such as stress, anxiety, confusion, and restlessness. Therefore, this book provides both academic and practical value, making it suitable for individuals interested in developing their minds through Buddhist practices